Biomass and abundance of termites in three remnant areas of Atlantic Forest in northeastern Brazil Biomassa e abundância de térmitas em três remanescentes de Mata Atlântica do Nordeste brasileiro - Alexandre Vasconcellos (Revista Brasileira de Entomologia, 2010)
Termite biomass and abundance were estimated in three remnant areas of Atlantic Forest in northeastern Brazil: Reserva Biológica de Pedra Talhada-RBPT (Alagoas State), Parque Estadual Dois Irmãos-PEDI (Pernambuco State), and Área de Proteção Ambiental Mata do Buraquinho-APMB (Paraíba State). A quantitative sampling of the termite assemblages present on trunks and leaf litter, in nests, and in the soil was undertaken during the months of June and July (rainy season) and November and December (dry season) of 2000. Thirty seven species of termites were encountered and quantified in the three remnant forest areas. The termite biomass varied from 10.09 to 11.30 g (fresh weight)/m² and abundance varied from 4911 to 5663 individuals/m². The subfamily Nasutitermitinae was dominant in terms of the number of species, biomass, and abundance. The soil-feeders were the most abundant at the three sites, while wood-feeders had the largest biomass at least at the PEDI and APMB sites. Among the microhabitats quantified, termites were most frequently encountered in the soil, being most heavily concentrated at depths of 0-20 cm. Two species stood out in terms of their biomass and abundance: Embiratermes parvirostris Constantino, on the soil, and Nasutitermes corniger (Motschulsky), on decomposing trunks and in nests. Estimates of biomass and abundance suggest that termites play an important role in the decomposition of the plant necromass in remnant forest areas of the Atlantic Forest in northeastern Brazil. A biomassa e a abundância de térmitas foram estimadas em três remanescentes de Mata Atlântica do Nordeste brasileiro: Reserva Biológica de Pedra Talhada-RBPT (Estado de Alagoas), Parque Estadual Dois Irmãos-PEDI (Estado de Pernambuco) e Área de Proteção Ambiental Mata do Buraquinho-APMB (Estado da Paraíba). Amostragens quantitativas da assembléia de térmitas foram realizadas em troncos, folhiço, ninhos e solo nos meses de junho e julho (estação chuvosa) e novembro e dezembro (estação seca) de 2000. Trinta e sete espécies de térmitas foram encontradas e quantificadas nos três remanescentes. A biomassa variou de 10,09 a 11,30 g (peso fresco)/m² e a abundância variou de 4911 a 5663 indivíduos/m². A subfamília Nasutitermitinae foi a dominante em número de espécies, biomassa e abundância. O grupo dos consumidores de húmus foi o mais abundante nos três sítios, enquanto os consumidores de madeira apresentaram a maior biomassa pelo menos na PEDI e na APMB. Entre os microhabitats quantificados, os térmitas foram encontrados principalmente no solo, estando fortemente concentrados entre 0 e 20 cm de profundidade. Duas espécies destacaram-se tanto pela biomassa como pela abundância: Embiratermes parvirostris Constantino, no solo, e Nasutitermes corniger (Motschulsky), nos troncos em decomposição e em ninhos. As estimativas de biomassa e de abundância sugerem que os térmitas desempenham um importante papel como mediadores do processo de decomposição da necromassa vegetal nos remanescentes de Mata Atlântica do Nordeste Brasileiro.